Integration of Islamic Values in STEM Learning in Secondary Schools - Baehaqi, Anan; Sukandar, Ahmad; Tata, Sumarta; Gunawan, Marina Trie Ramadhany; Hani, Aan (International Education Trend Issues, 2024)
This research aims to explore the integration of Islamic values into STEM (Science, Technology, Engineering, and Mathematics) learning in secondary schools. In the era of globalization, STEM education is becoming increasingly important to prepare students for future challenges. However, education that only focuses on technical aspects without paying attention to spiritual and moral values can result in disorientation in students' lives. Therefore, this study proposes an approach that combines scientific aspects with Islamic values to create holistic learning. The research method used is qualitative with a literature study approach. Data was collected through observation and analysis of curriculum documents. The results of the study show that the integration of Islamic values in STEM learning can improve students' understanding of the relationship between science and religious teachings, as well as motivate them to apply the knowledge learned in daily life in accordance with Islamic principles. Consistent implementation and support from all schools are needed to ensure the sustainability of this program.